Pengujian Skala Efikasi Diri Perawat di RS X Menggunakan Model Rasch - Satria Efandi; Riva Nadia Putri (Psyche 165 Journal, 2022)
Hospital services that require dedication to the patient's health conditions must be carried out with full responsibility and qualified competence. One profession that requires good service skills is the nursing profession. Nurses must have confidence in their ability to provide the best service to patients in order to ensure that every treatment action is carried out effectively and optimally. Therefore, the task of providing services for nurses in hospitals requires a sense of ability to succeed (self-efficacy) in each job to be able to provide professional services. Self-efficacy is a form of self-confidence that a person has in his ability to carry out or complete tasks, achieve goals, and overcome obstacles and failures. Until this research was made, there had been no studies that tested using the Rasch model on self-efficacy scales in work contexts, especially among nurses in hospitals. Therefore this study aims to examine as well as test the development of self-efficacy instruments for nurses using the Rasch analysis model. The subjects in this study were 68 nurses who were actively working at hospital X. Based on the results of the Rasch model analysis carried out using the WINSTEP statistical processing program, 12 items (out of 24 items) met the item model fit level, with an alpha reliability coefficient moving from 0.92. Overall, it can be concluded that the items in this nurse self-efficacy instrument have valid and reliable psychometric attributes to be used in research